De criminal a ícono: la evolución del legado de pablo escobar en espacios públicos y medios - Neyder Felipe Campos Sánchez; Carlos Mario Paredes Pérez; Caren Yulieth Carreño Delgado (Mundo Fesc)
This study analyzes how Pablo Escobar's image has been portrayed in popular culture and the media, and how this representation has influenced the way people remember Colombian history. In movies, television programs, and books, the leader of the Medellín Cartel, who committed many evil deeds, is portrayed in a confusing light. Programs like *Narcos* have made him seem more interesting and understandable, prompting discussions about how much we should admire his criminal past. The grief of his victims has been diminished by narco-tourism in Medellín and the marketing of his image, using the most shocking moments of his life, although certain groups saw this as beneficial.